2015
DOI: 10.3762/bjoc.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent versus domino reactions: One-pot free-radical synthesis of β-amino-ethers and β-amino-alcohols

Abstract: SummaryFollowing an optimized multicomponent procedure, an aryl amine, a ketone, and a cyclic ether or an alcohol molecule are assembled in a one-pot synthesis by nucleophilic radical addition of ketyl radicals to ketimines generated in situ. The reaction occurs under mild conditions by mediation of the TiCl4/Zn/t-BuOOH system, leading to the formation of quaternary β-amino-ethers and -alcohols. The new reaction conditions guarantee good selectivity by preventing the formation of secondary products. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…C­(sp 3 )–H functionalization of ethers through H atom abstraction has recently achieved great development; however, most of the previous works required a stoichiometric amount of strong oxidants to produce and regenerate the H-abstractors . These methods are less suitable for the redox-neutral catalytic reaction of imines, especially those with alkyl substituents …”
mentioning
confidence: 99%
“…C­(sp 3 )–H functionalization of ethers through H atom abstraction has recently achieved great development; however, most of the previous works required a stoichiometric amount of strong oxidants to produce and regenerate the H-abstractors . These methods are less suitable for the redox-neutral catalytic reaction of imines, especially those with alkyl substituents …”
mentioning
confidence: 99%
“…Furthermore, the reaction was perfectly stereospecific and the product was a 1′-amino-tetrahydrofuran, a family of molecules found extensively in medicinal chemistry patents. A search of the literature revealed that, by far, the most common method for the synthesis of 1′-amino-tetrahydrofurans is via radical additions into imines (Scheme B). Other approaches include hydrogenation of furans and cyclization of linear diols (Scheme B). , While these methods are inspiring, they suffer from lengthy starting material preparations or from a lack of stereoselectivity during product formation. To our surprise, the ring opening of aziridines by pendant free or protected alcohols has only been sparingly explored for the synthesis of 1′-amino-tetrahydrofurans.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the literature revealed that, by far, the most common method for the synthesis of 1'-amino-tetrahydrofurans is via radical additions into imines (Scheme 2B). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Other approaches include hydrogenation of furans [29][30][31] and cyclization of linear diols (Scheme 2B). 32,33 While these methods are inspiring, they suffer from lengthy starting material preparations or from a lack of stereoselectivity during product formation.…”
Section: Introductionmentioning
confidence: 99%